Assessing the Administrative Sanctions Regime for Insider Trading in China: An Empirical Approach. Issue 2 (21st January 2016) - WENG, Charlie Xiao-chuan; JIA, Jingwei
Abstract: The Chinese Securities Regulatory Commission (CSRC) has significantly revised its overall market supervision framework over the last two decades. China's insider trading laws, however, remain broad and abstract, while most enforcement measures take place inside a black box. These circumstances have led to an unpredictable and ineffective enforcement regime. This article examines all administrative sanctions cases from 2000 to 2013 in order to examine the CSRC's actual enforcement practices. This data shows that the agency has a history of inconsistent enforcement, which stands as a warning against the consequences of unpredictable regulation. Moreover, it argues that the Commission's current approach to recognizing illegal gains is both unreasonable and illegal, and that the CSRC has failed to adequately enforce actions for loss evasion cases. By adjusting enforcement policy to take these considerations into account, the CSRC would significantly improve the efficacy of the sanctions regime in China.